Assessment of socio-environmental sustainability and resilience in a rural settlement in Southeast Pará, Amazon - Santos, Janaira Almeida; Lucas, Flávia Cristina Araújo (Sustainability in Debate, 2025)
The study conducted at the Castanhal Araras Settlement Project in São João do Araguaia, Pará, Brazil, assessed socio-environmental sustainability using a mixed methods approach. The research was grounded in diagnostic analysis of agrarian systems and the Framework for the Assessment of Natural Resource Management Systems Incorporating Sustainability Indicators (Mesmis). Data collection involved field notes, interviews, photographic records and participant observation. The results indicated a ‘compromised’ level of sustainability in both the social (score: 37) and environmental (score: 39) dimensions. On the social front, strengths included the use of family labour and a generally satisfactory quality of life. However, there were notable challenges regarding access to water, social inclusion, and community participation. Environmentally, while positive practices like diversified livelihoods and partial conservation efforts were present, they were offset by issues like pesticide use, soil compaction, the use of fire and extensive cattle ranching. Resilience was observed through the adoption of agroforestry systems and resourcefulness in agricultural practices. To address these challenges, it is essential to strengthen environmental education, enhance community engagement, and promote sustainable land management practices.